Hemodynamic response to exercise is impaired in individuals with Parkinson's disease - Fernandes, Bianca [UNESP]; Barbieri, Fabio A.; Marçal, Isabela R. [UNESP]; Doamaral, Vanessa T. [UNESP]; Simieli, Lucas; Penedo, Tiago; Ciolac, Emmanuel G. [UNESP] (Edizioni Minerva Medica, 2022)
BACKGROUND: The aim of this study was to assess hemodynamic and cardiac autonomic response to high-intensity interval exercise (HIIE) versus moderate-intensity continuous exercise (MICE) in individuals with Parkinson's disease (PD). METHODS: Twelve individuals (six men) with PDwere randomly assigned to perform HIIE(4 min of warm-up followed by 21 min alternating 1 min at levels 15-17 with 2 min at levels 9-11 of rating of perceived exertion [RPE] in a cycle ergometer), MICE(4 min of warm-up followed by 26 min at levels 11-14 of RPEin a cycle ergometer) and control (CON; 30 min of sitting rest) interventions in separate days. Heart rate (HR), blood pressure (BP), endothelial reactivity and heart rate variability (HRV) were assessed before, immediately after and 45 min after each intervention. HRand exercise workload were measured during each intervention. RESULTS: Despite the within (high- vs. low-intensity intervals of HIIE) and between (HIIEvs. MICE) differences in workload during exercise sessions, HRwas not different between high- (average HR=98±18 bpm) and low-intensity (average HR97±19 bpm) intervals of HIIE, as well as between HIIE (average HR=97±18 bpm) and MICE (average HR=93±19 bpm) throughout the exercise. There were significant, but small, increases (P<0.01) in HRand systolic BPat post HIIEand MICE, which returned to levels similar to preintervention during recovery. There were no within- and between-intervention differences in diastolic BP, endothelial reactivity and HRV. CONCLUSIONS: The present results suggest that hemodynamic response to exercise is impaired in individuals with PD.
Keywords: Blood pressure; Endothelium; Exercise; Heart function tests